2013
DOI: 10.1371/journal.pone.0069737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of External Potassium (K) Supply on Drought Tolerances of Two Contrasting Winter Wheat Cultivars

Abstract: BackgroundDrought is a common stress limiting crops growth and productivities worldwide. Water deficit may increase cellular membrane permeability, resulting in K outflow. Internal K starvation may disorder plant metabolism and limit plant growth. However, it is seldom reported about the effects of external K on drought tolerance of contrasting wheat cultivars.Methodology/Principal FindingsA hydroponics experiment was carried out in a non-controlled greenhouse. Seedlings of drought-tolerant SN16 and intolerant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 40 publications
(45 reference statements)
6
27
0
1
Order By: Relevance
“…Our research indicated that the concentrations of K + in various cotton organs under the OPT-W treatment were higher than that under the OPT-W-K treatment ( Table 2). Wei et al (2013) found that external K may increase plant drought tolerance of wheat by enhancing internal K + concentration under drought stress, which was consistent with our result. Soil moisture can also influence the uptake rate of K via affecting its mobility from the soil to the root surface.…”
Section: Discussionsupporting
confidence: 92%
“…Our research indicated that the concentrations of K + in various cotton organs under the OPT-W treatment were higher than that under the OPT-W-K treatment ( Table 2). Wei et al (2013) found that external K may increase plant drought tolerance of wheat by enhancing internal K + concentration under drought stress, which was consistent with our result. Soil moisture can also influence the uptake rate of K via affecting its mobility from the soil to the root surface.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, K is essential for cell turgor maintenance via osmotic adjustment (DaCosta and Huang, 2006) and transpiration control via stomatal regulation (Jin et al, 2011) under drought stress. In a hydroponic study, external supply of K in the nutrient medium has been shown to improve drought tolerance in wheat cultivars by improving water potential, chlorophyll contents, gas exchange and an effective reactive oxygen species scavenging (Wei et al, 2013). Foliar application of K is also shown to improve maize yield under rainfed conditions (Anees et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the malondialdehyde (MDA) content and the activities of antioxidant enzymes, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), were extensively applied as the sensitive biomarkers for the damnification of plants in contaminated soil or adversity stresses (Sun et al 2010;Wei et al 2013). Thus, this provides the possibility to employ the antioxidant enzymes and MDA to further investigate the potential toxicity of biochar to plants.…”
Section: Introductionmentioning
confidence: 99%